The interaction between vegetation and near-surface water in a wetland system, Stellenbosch, South Africa - Kareko, John K.(John Kariuki) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004.